Isolasi dan Uji Aktivitas Antioksidan Metabolit Sekunder dari Ekstrak Etil Asetat Kulit Batang Kangkang Katup (Bauhinia semibifida Roxb) - Fadhli, Haiyul; Lukman, Anita; Adawiyah, Robiatun (Al-Kimia, 2020)
Antioxidant was a compound which possessed an activity as scavenger of free radicals. This study was aimed to examine the antioxidant activity of ethyl acetate fraction and isolated compound from stem barks of Bauhinia semibifida Roxb. Samples extracted by gradual maceration with n-hexane solvent, ethyl acetate and methanol respectively. Isolation was carried out using Vacuum Liquid Chromatrography and purification by column chromatography with Sephadex LH-20. Isolated compound (BS) obtained was ivory crystalline with melting point 163-1650C. The analysis of FT-IR spectra, UV spectra and the result of qualitative test by Liebermann Burchard reagent were is shown positive as a terpenoid. Antioxidant activity were evaluated by using DPPH method for ethyl acetate fraction and isolation compound in serial concentration of 1000; 500; 250; 125; 62,5; 31,25 ug/mL. The result found that ethyl acetate fraction (f4 and f11) of stem barks of Bauhinia semibifida showed antioxidant activity with IC50 value of >1000 ug/mL; 179 ug/mL. In conclusion, F11 from ethyl acetate extract from stem barks of Bauhinia semibifida Roxb. exhibited an activity as scavenger of free radicals from DPPH. Keywords: Antioxidant, Bauhinia semibifida Roxb, IC50, VLC